“NINGUÉM FALA QUE O CARA É CULPADO”: IDENTIDADES DE GÊNERO FEMININO A PARTIR DO SIGNO VIOLÊNCIA NO SITE DA REVISTA MARIE CLAIRE - Israel, Fernanda Aparecida (2015)
This paper seeks to promote discussions on the identity of inserted female gender in a specific written context of post-modernity, the Internet, cropped at the World Women session Marie Claire magazine's website. The Marie Claire magazine caught my attention by the slogan "Chic is to be smart." In this way, I realized that a magazine that tries to promote women beyond the physical appearance and consumer relations, has interesting objects to be analyzed. The dissertation is structured into three main chapters. The first, entitled Speech Genres, I discuss the concept of postulate speech genres in the work of Bakhtin, and reflect on what would be the so-called internal and external factors of the statement. In this chapter we present also some characteristics of the statement and its relation to the genres published in the studied women's magazine. In chapter two, entitled Post-modernity and its emergency: identity and gender issues, promote, in the first session, Identities, reflections on the context of post-modernity and the possibilities of subject identity arising from this period, from Stuart Hall (2006). In the second session, the social gender as a category under review, present discussions on female social gender, focusing on its way to legitimize theory in science, from Guacira Lopes Louro (1997) and Judith Butler (1999). In the third session, magazine holder: the female press from the seventeenth century and the subtopic Marie Claire magazine, I present a brief history of the press aimed at women in the world, emphasizing some discursive aspects that she carried and what aspects remain in current press as well as show some characteristics in the historic building of Marie Claire magazine. In the third chapter, entitled They: the World's Women, do analyzes of the main theme Women in abusive relationships - cut in fifteen texts - in which promote a dialogue between the sign violence and discourse on socially constructed gender identity. Public / private relationships, guilt / vulnerability, westernization, the feminist movement shifts, empowerment and expansion of the concept of women's health, are some results. Finally, I do the considerations about the research.